Pharmacokinetic modeling of sulfamethoxazole-trimethoprim and sulfadiazine-trimethoprim combinations in broilers - Marine Boulanger; Jean-François Taillandier; Jérôme Henri; Mathias Devreese; Siegrid De Baere; Aude A. Ferran; Alexis Viel (Poultry Science, 2024)
ABSTRACT: Sulfonamides (S) are old bacteriostatic antibiotics which are widely prescribed in combination with trimethoprim (TMP) for the treatment of various diseases in food-producing animals such as poultry. Nowadays, the 1:5 dose ratio of TMP/S used in broilers is a direct transposition of the ratio determined in Human decades ago for TMP/sulfamethoxazole (SMX), aiming to obtain a supposed synergistic plasma concentration ratio of 1:19. However, major pharmacokinetics (PK) differences exist according to the sulfonamide used in the combination. Here, we generated new PK data in broilers after a cross-over design with IV and the oral administration of 2 major sulfonamides, sulfadiazine (SDZ) and SMX, in combination with TMP, and analyzed the data via a population pharmacokinetic (popPK) modeling approach. Results showed that TMP has a greater plasma to tissue distribution than both sulfonamides with a higher volume of distribution (0.51 L/kg for SDZ, 0.62 L/kg for SMX and 3.14 L/kg for TMP). SMX has the highest elimination half-life (2.83 h) followed by SDZ and TMP (2.01 h and 1.49 h, respectively). The oral bioavailability of the 3 molecules was approximately 100%. Bodyweight could explain some of the inter-individual variability in the volume of distribution of SDZ and SMX and the clearance of SDZ and TMP, as heavier broilers have higher typical values. Monte Carlo simulations of a large virtual broiler population (n = 1,000) showed that the targeted plasma ratio of TMP:S of 1:19 was rarely or never reached at the individual level for both combinations at the marketed doses and greatly varies over time and between individuals, questioning the relevance of the 1:5 dose ratio for current formulations of TMP/S.